Replacement of conventional doxorubicin by pegylated liposomal doxorubicin is a safe and effective alternative in the treatment of non-Hodgkin's lymphoma patients with cardiac risk factors - Schmitt, Christian Johannes; Dietrich, Sascha; Ho, Anthony Dick; Witzens-Harig, Mathias (Annals of hematology, 2012)
Anthracyclines are a major component in the therapy of non-Hodgkin's lymphoma. However, due to their cardiac toxicity potential, curative and palliative treatment is often limited in patients with preexisting cardiac dysfunction. Liposomal doxorubicin formulations have been described to be less cardiotoxic than conventional doxorubicin. In the current study, we analyzed the efficacy and toxicity of pegylated liposomal doxorubicin (PLD) as constituent of the cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) regimen replacing conventional doxorubicin in 21 patients with impaired cardiac left ventricular ejection fraction or preexisting cardiac risk factors and established diagnosis of diffuse large B cell lymphoma (n = 15), mantle cell lymphoma (n = 3), follicular lymphoma (n = 1), and T cell lymphoma (n = 2). Overall and complete response rate were 85% and 40%, respectively. Event-free survival and overall survival after 2 years were 58%. One lethal event of acute cardiac death occurred during the first cycle in a patient with transposition of the big arteries, atrial flutter, and mitral valve regurgitation. In the remaining 20 patients, no deterioration of myocardial function was observed in echocardiography performed before and after treatment. Seven cases of grade III-IV hematological toxicity were observed as well as four episodes of neutropenic fever leading to hospitalization. No infection-related death occurred. However, 25% of patients developed a hand-foot syndrome (HFS) leading to discontinuation of treatment. Importantly, the incidence of HFS increased considerably when PLD doses of 15 mg/m2/week were exceeded. We conclude that replacing conventional doxorubicin with PLD in polychemotherapy regimens such as CHOP is an efficient alternative in the treatment of patients with preexisting cardiac dysfunction. However, we recommend that PLD dose should not exceed 15 mg/m2/week. The rationale for the use of non-pegylated liposomal doxorubicin formulations should be evaluated in further studies.